2009
DOI: 10.1029/2009jc005359
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium shoreline response: Observations and modeling

Abstract: [1] Shoreline location and incident wave energy, observed for almost 5 years at Torrey Pines beach, show seasonal fluctuations characteristic of southern California beaches. The shoreline location, defined as the cross-shore position of the mean sea level contour, retreats by almost 40 m in response to energetic winter waves and gradually recovers during low-energy summer waves. Hourly estimates of incident wave energy and weekly to monthly surveys of the shoreline location are used to develop and calibrate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
384
5
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(411 citation statements)
references
References 37 publications
17
384
5
5
Order By: Relevance
“…Despite having a detailed set of data with morphological and hydrodynamic characteristics, it remains difficult to provide a conclusive statement on the theoretical effect(s) of storm clustering. One might expect a depleted beach to be more prone to erosion but recent work (Yates et al, 2009) indicates the opposite: since beaches always tend to an equilibrium shape and since a storm tends to push the beach far from equilibrium, sequences of storms should be less and less effective in driving the beach away from equilibrium. Our results have elements that are consistent with the simple model of Yates et al (2009) although we also suggest that other characteristics of the 'storm chronology' such as tidal stage and surfzone characteristics are at least as important as wave height and are needed in such a model in order for it to be more universally applicable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite having a detailed set of data with morphological and hydrodynamic characteristics, it remains difficult to provide a conclusive statement on the theoretical effect(s) of storm clustering. One might expect a depleted beach to be more prone to erosion but recent work (Yates et al, 2009) indicates the opposite: since beaches always tend to an equilibrium shape and since a storm tends to push the beach far from equilibrium, sequences of storms should be less and less effective in driving the beach away from equilibrium. Our results have elements that are consistent with the simple model of Yates et al (2009) although we also suggest that other characteristics of the 'storm chronology' such as tidal stage and surfzone characteristics are at least as important as wave height and are needed in such a model in order for it to be more universally applicable.…”
Section: Discussionmentioning
confidence: 98%
“…Both hypotheses are viable and in this context recent data-driven models have shown that shoreline erosion tends to diminish if erosive conditions are maintained (Yates et al, 2009). At the same time, because of the difficulty in collecting an appropriate dataset, little is known about the alongshore variability in beach response to storms.…”
Section: Introductionmentioning
confidence: 99%
“…4). Although the magnitude of beach response in reef environments is much less than sandy environments, the underlying forcing mechanism appears to be similar, with the magnitude of divergence (or disequilibrium) of nearshore wave heights from typical nearshore wave heights a key factor determining storm-induced beach response (e.g., Yates et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…It may be suggested that the change in wave conditions is more relevant in driving bar morphological change than the absolute values of the wave parameters: e.g., all offshore migration events occurred following an increase in H/L, whereas all onshore migration events coincided with falling H/L values. If changes in the wave conditions are more relevant in driving bar behaviour than actual wave parameters, an equilibrium type of response model, involving deviations from antecedent wave conditions is worth pursuing (e.g., Yates et al, 2009;Davidson et al, 2013;Castelle et al, 2014). Following Davidson et al (2013), bar dynamics are related to the product of the wave energy flux P and a disequilibrium term (Ω m -Ω), where Ω m is the background antecedent value for Ω, and Ω represents the instantaneous value.…”
Section: Beach and Nearshore Morphologymentioning
confidence: 99%